Transpacific imbalances and macroeconomic codependency - Willem Thorbecke (Asian Development Bank Institute (ADBI), 2011)
Current account deficits in the United States (US) and current account surpluses in East Asia are an enduring part of the global economic landscape. They are supported by low saving in the US and by reserve accumulation in Asia. This paper argues that this strategy is causing macroeconomic problems for the People's Republic of China (PRC). Inflation is rising, and interest rates are set too low because the yuan is closely linked to the US dollar. Low interest rates have fueled overinvestment in physical capital and rising real estate prices. They also cause savers to earn negative returns on their bank deposits. Greater exchange rate flexibility would allow more decoupling between the PRC's interest rates and US interest rates, helping the People's Bank of China to implement monetary policy that is appropriate for the PRC. Since exchange rate appreciations would be contractionary for the PRC, they should be combined with domestic absorption-increasing policies such as spending on education, health care, and urban transportation. Interest rates and exchange rates that are more determined by market forces would also help the PRC to move away from an overly capital-intensive growth path to one that is more beneficial for smaller firms and ordinary workers.
Keywords: F30; F32; 330; Zahlungsbilanzungleichgewicht; USA; Asien; Währungsreserven; Fester Wechselkurs; US-Dollar; Renminbi; Makroökonomischer Einfluss; China; Wirtschaftswachstum; Asien